2019
DOI: 10.2174/0929866526666190405123422
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of the Angiotensin-Converting Enzyme 2 Activator Dize in Renovascular Hypertension

Abstract: Background: Angiotensin Converting Enzyme (ACE) 2 is an important modulator of the Renin Angiotensin System (RAS) and the RAS plays a central role in renovascular hypertension. Very few studies investigated the role of components of the counterregulatory RAS axis (ACE2, Ang-(1-7) and Mas receptor) in renovascular hypertension and the results are controversial. Objective: The aim of this study was to investigate the effects of Diminazene Aceturate (DIZE) administration on renal function and renal inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…Thus, the current data provided evidence that the hypothalamic-pituitary-adrenal (HPA) axis is activated in non-critical COVID-19 patients but suppressed in critical patients. Furthermore, DIZE increases ACTH secretion in vitro, which could serve as the potential therapy for critical COVID-19 patients [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current data provided evidence that the hypothalamic-pituitary-adrenal (HPA) axis is activated in non-critical COVID-19 patients but suppressed in critical patients. Furthermore, DIZE increases ACTH secretion in vitro, which could serve as the potential therapy for critical COVID-19 patients [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…A regulator of the cardiovascular system is the renin-angiotensin system (RAS), a system exhibited on various tissues and cells, which has been established as a key regulator of the body’s hormonal and fluid balance system. The RAS is usually pharmacologically targeted for the management of heart failure [ 34 , 35 , 36 , 37 ], diabetes [ 38 , 39 ], and hypertension/blood pressure control [ 40 , 41 , 42 ]. The main effector of RAS is angiotensin II (AngII), which is produced by angiotensin-converting enzyme (ACE) within the circulation or in ACE-expressed cells [ 43 , 44 , 45 ].…”
Section: Effects Of Taurine On the Cardiovascular Systemmentioning
confidence: 99%
“…More recently, our research group found that oral administration of another ACE2 activator, the compound diminazene aceturate (DIZE), attenuated renal dysfunction and reduced the levels of myeloperoxidase and N-acetyl-beta-D-glucosaminidase, cytokines and chemokines and increased urinary nitrate/nitrite levels in 2 kidney-1 clip hypertensive rats (22). The role of DIZE in a gender-based I/R kidney injury was analyzed in a study conducted by Malek et al Downloaded from http://portlandpress.com/clinsci/article-pdf/doi/10.1042/CS20201022/897620/cs-2020-1022.pdf by guest on 26 November 2020 (23).…”
Section: Introductionmentioning
confidence: 99%